From Gabriel and Lucifer : a cultural history of angels - Rees, Valery, 1947- (I.B. Tauris ; Distributed in the US and Canada exclusively by Palgrave Macmillan, 2013)
Fiery the angels fell; slow thunder rolled around their shores, burning with the fires of Orc.' Whether in recent popular culture, or back across countless centuries, angels have perpetually enthralled and even terrified us. 'Every single angel is terrible, ' wrote the German Romantic poet Rilke: 'and so I hold myself back from the dark bird-cry of my anguished sobbing.' For sceptics, angels may be no more than metaphors: poetic devices to convey, at least for those with a religious sensibility, an active divine interest in creation. But for others, angels are absolutely real creatures: manifes.